Deciphering the let-7c-5p/RRM2 axis in lung adenocarcinoma: expression, prognosis, and immune landscape implications - Liu, Jinlong; Wu, Jinying; Han, Yu; Li, Lele; Bian, Xingbo; Sun, Xialin; Bian, Xuefeng; Sun, Xin (Frontiers in Oncology, 2025)
ObjectiveLung adenocarcinoma (LUAD) is a subtype of non-small cell lung cancer with a poor prognosis. Ribonucleotide reductase subunit M2 (RRM2) has been implicated in the progression of various cancers, but its role in LUAD remains underexplored. This study aims to elucidate the expression patterns, clinical significance, and regulatory mechanisms of RRM2 in LUAD.MethodsWe conducted a comprehensive analysis of RRM2 expression using data from the Genomic Data Commons Data Portal and The Cancer Genome Atlas. Survival analysis was performed using the KM plotter tool. The starBase database was utilized to identify miRNAs associated with RRM2. Single-cell RNA sequencing data was analyzed to explore the correlation between RRM2 and immune cell infiltration. In vitro experiments were conducted to validate the regulatory role of let-7c-5p on RRM2 in LUAD cell lines.ResultsWe found that the expression of RRM2 in LUAD tissues was significantly higher than in normal tissues, and its expression was associated with advanced pathological stage and poor overall survival. Additionally, we identified Let-7c-5p as a potential upstream regulator of RRM2, which is down-regulated in LAUD and negatively correlated with RRM2 expression. In vitro experiments showed that overexpression of let-7c-5p reduced RRM2 levels and inhibited LUAD cell proliferation and migration. Moreover, RRM2 expression was positively correlated with the infiltration of certain immune cells, suggesting its role in modulating the tumor immune microenvironment.ConclusionsOur findings suggest that RRM2 is closely associated with the malignant progression of LUAD and may serve as a potential prognostic biomarker with clinical relevance. Furthermore, the let-7c-5p/RRM2 regulatory axis may play an important role in the development and progression of LUAD, representing a promising therapeutic target that warrants further in-depth investigation.